Optimal Location and Size of Multi-distributed Generation with Minimization of Network Losses - Barnwal A.K.; Singh S.; Verma M.K. (My University, 2025)
Distribution system is one of integral part of complex power system. Power losses in distribution system branches are very high rather than power losses in transmission system branches. These higher losses lead to higher operational cost in distribution system. The advancement of technology using distributed generations has been proved to be very important in optimizing network losses, environment pollution, and reliability of power systems. The DG allocation is a mixed-integer optimization problem with nonlinearity associated. In this paper, the work optimal size location and power factor of single and multiple placements of different distributed generators have been presented. Distribution network loss has been minimized for optimal power factor, size, and location of distributed generator to be optimized. Optimum size and minimum loss have been determined. Results thus obtained have been compared with the results in the literature. The proposed method has been validated on the IEEE33-bus test system. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.